Effectiveness of vitamin c in the management of viral infections in adults - Kozioł, Magdalena; Cąkała, Marlena; Podgórniak, Kamila; Zajkowska, Aleksandra; Witkowska, Maria; Skotnicka, Joanna (Quality in Sport, 2024)
Abstract Introduction: Vitamin C, ascorbic acid, is an essential water-soluble nutrient. Vitamin C has important anti-inflammatory, immunomodulating, antioxidant, antithrombotic and antiviral properties. The role of vitamin C in preventing and treating the upper respiratory tract infections has been controversial since the dual Nobel laureate Linus Pauling published a book in 1970 claiming that vitamin C prevents and alleviates symptoms of common cold. Aim of the study: The aim of our study was to evaluate the efficacy of vitamin C administration during viral infections in the adult population. Brief description of the state of knowledge: In the analyzed studies, vitamin C supplementation has been found to play a role in respiratory defense mechanisms for specific groups of patients with upper respiratory tract infections. While there is some promise in the use of vitamin C for the treatment of COVID-19, current evidence for its efficacy in pneumonia is weak, but vitamin C may still have a place in treatment, particularly for patients with low levels of the vitamin. Additional research is necessary to determine the efficacy of administering vitamin C for the treatment of pneumonia, the common cold, and COVID-19. Conclusions: The available evidence from the studies does not provide clear proof of the efficacy of vitamin C supplementation in preventing or treating viral infections such as the common cold, COVID-19 or pneumonia. Further studies, particularly randomized clinical trials, are necessary to demonstrate its effectiveness in specific viral infections. The current evidence is insufficient to recommend the use of vitamin C for preventing or treating viral infections in the general population. Key words: vitamin C; ascorbic acid; viral infections; common cold; COVID-19; pneumonia